Manfaat Akuntansi Forensik - Jeanne Asteria Wawolangi (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
Forensic Accounting is a specific knowledge which related fraud. The enterprises want to implement Forensic Accounting with audit investigation as detection all the fact of crime especially to judge/justice. This research as a descriptive qualitatif research which take many informan from the student of Economic Faculty, Accounting Program Study and the results show that many informan give perception that Forensic Accounting is very usefull and the lectures should teach good behavior knowledge to all the students, so the student will get good behavior and high responsibility. Finally we hope the situation of economic in Indonesia will succesefull and wealth.